Developing Literature Program for Children - Yasmin Farani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2016)
Education today has given great attention on children and their phsycological state. However, it is hardly given attention that books as the material for teaching in child education play as important role as those for adults. This is more urgent especially when televisions or visualized media have much influence on the children. This certainly leads to the consequence that children today might not manage to develop what the cognitivists call cognitive control-system (see Swaan, 1993, Alberson(1981), Van Dijk and Kintsch(1983). This paper, in general aims at demonstrating that literature program for children today can give more humanistic picture to education or in other words it will treat children education not as mechanistic as before.